h - Daniilidis, Kostas; Maragos, Petros; Paragios, Nikos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The six-volume set comprising LNCS volumes 6311 -- 6316 constitutes the refereed proceedings of the 11th European Conference on Computer Vision, ECCV 2010, held in Heraklion, Crete, Greece, in September 2010. The 325 revised papers presented were carefully reviewed and selected from 1174 submissions. The papers are organized in topical sections on object and scene recognition; segmentation and grouping; face, gesture, biometrics; motion and tracking; statistical models and visual learning; matching, registration, alignment; computational imaging; mutli-view geometry; image features; video and event characterization; shape representation and recognition; stereo; reflectance, illumination, color; medical image analysis.
Spotlights and Posters W1 -- Kernel Sparse Representation for Image Classification and Face Recognition -- Every Picture Tells a Story: Generating Sentences from Images -- An Eye Fixation Database for Saliency Detection in Images -- Face Image Relighting using Locally Constrained Global Optimization -- Correlation-Based Intrinsic Image Extraction from a Single Image -- ADICT: Accurate Direct and Inverse Color Transformation -- Real-Time Specular Highlight Removal Using Bilateral Filtering -- Learning Artistic Lighting Template from Portrait Photographs -- Photometric Stereo from Maximum Feasible Lambertian Reflections -- Part-Based Feature Synthesis for Human Detection -- Improving the Fisher Kernel for Large-Scale Image Classification -- Max-Margin Dictionary Learning for Multiclass Image Categorization -- Towards Optimal Naive Bayes Nearest Neighbor -- Weakly Supervised Classification of Objects in Images Using Soft Random Forests -- Learning What and How of Contextual Models for Scene Labeling -- Adapting Visual Category Models to New Domains -- Improved Human Parsing with a Full Relational Model -- Multiresolution Models for Object Detection -- Accurate Image Localization Based on Google Maps Street View -- A Minimal Case Solution to the Calibrated Relative Pose Problem for the Case of Two Known Orientation Angles -- Bilinear Factorization via Augmented Lagrange Multipliers -- Piecewise Quadratic Reconstruction of Non-Rigid Surfaces from Monocular Sequences -- Extrinsic Camera Calibration Using Multiple Reflections -- Probabilistic Deformable Surface Tracking from Multiple Videos -- Theory of Optimal View Interpolation with Depth Inaccuracy -- Practical Methods for Convex Multi-view Reconstruction -- Building Rome on a Cloudless Day -- Camera Pose Estimation Using Images of Planar Mirror Reflections -- Element-Wise Factorization for N-View Projective Reconstruction -- Learning Relations among Movie Characters: A Social Network Perspective -- Scene and Object Recognition -- What, Where and How Many? Combining Object Detectors and CRFs -- Visual Recognition with Humans in the Loop -- Localizing Objects While Learning Their Appearance -- Monocular 3D Scene Modeling and Inference: Understanding Multi-Object Traffic Scenes -- Blocks World Revisited: Image Understanding Using Qualitative Geometry and Mechanics -- Discriminative Learning with Latent Variables for Cluttered Indoor Scene Understanding -- Spotlights and Posters W2 -- Visual Tracking Using a Pixelwise Spatiotemporal Oriented Energy Representation -- A Globally Optimal Approach for 3D Elastic Motion Estimation from Stereo Sequences -- Occlusion Boundary Detection Using Pseudo-depth -- Multiple Target Tracking in World Coordinate with Single, Minimally Calibrated Camera -- Joint Estimation of Motion, Structure and Geometry from Stereo Sequences -- Dense, Robust, and Accurate Motion Field Estimation from Stereo Image Sequences in Real-Time -- Estimation of 3D Object Structure, Motion and Rotation Based on 4D Affine Optical Flow Using a Multi-camera Array -- Efficiently Scaling Up Video Annotation with Crowdsourced Marketplaces -- Robust and Fast Collaborative Tracking with Two Stage Sparse Optimization -- Nonlocal Multiscale Hierarchical Decomposition on Graphs -- Adaptive Regularization for Image Segmentation Using Local Image Curvature Cues -- A Static SMC Sampler on Shapes for the Automated Segmentation of Aortic Calcifications -- Fast Dynamic Texture Detection -- Finding Semantic Structures in Image Hierarchies Using Laplacian Graph Energy -- Semantic Segmentation of Urban Scenes Using Dense Depth Maps -- Tensor Sparse Coding for Region Covariances -- Improving Local Descriptors by Embedding Global and Local Spatial Information -- Detecting Faint Curved Edges in Noisy Images -- Spatial Statistics of Visual Keypoints for Texture Recognition -- BRIEF: Binary Robust Independent Elementary Features -- Multi-label Feature Transform for Image Classifications.
Keywords: Computer science; Computer software; Computer vision; Computer graphics; Optical pattern recognition; Biometrics; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Pattern Recognition; Biometrics; Computer Graphics; Algorithm Analysis and Problem Complexity